2018
DOI: 10.1016/j.ijid.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B virus and Hepatitis D virus Coinfection in Western Burkina Faso and molecular characterization of the detected virus strains

Abstract: Our study showed a high HBsAg prevalence, but a low rate of HDV co-infection in HBsAg carriers from western Burkina Faso. The predominance of HBV genotype E in the country was confirmed. Our findings contribute to a better understanding of the burden of HBV and HDV infection in western Burkina Faso.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
0
14
0
7
Order By: Relevance
“…Extreme caution should be exercised regarding the interpretation of the estimated prevalence for South America, due to selection biases observed during study review. These biases have been caused by the absence of information from several countries located far from the Amazon basin, as well as the use of data collected by studies conducted in the 1980s 1,2,5,6 and 1990s 3,4,[7][8][9][10][11][12][13][14][15][16][17]21 , which led to an overestimation of HDV infection cases in the studied area.…”
Section: /12mentioning
confidence: 99%
See 3 more Smart Citations
“…Extreme caution should be exercised regarding the interpretation of the estimated prevalence for South America, due to selection biases observed during study review. These biases have been caused by the absence of information from several countries located far from the Amazon basin, as well as the use of data collected by studies conducted in the 1980s 1,2,5,6 and 1990s 3,4,[7][8][9][10][11][12][13][14][15][16][17]21 , which led to an overestimation of HDV infection cases in the studied area.…”
Section: /12mentioning
confidence: 99%
“…Most of the studies included in this meta-analysis presented moderate methodological quality in relation to established criteria quality 1,2,[4][5][6][7]9,[12][13][14][15][16][17][18][19][20]23,[26][27][28][29][30] . The information provided in this review revealed that almost all studies had cross-sectional designs [2][3][4][5][8][9][10][11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] as they fit prevalence studies; therefore, they did not provide information on relative time of exposure and outcome. A strength of this r...…”
Section: /12mentioning
confidence: 99%
See 2 more Smart Citations
“…Data on HBV and HCV in West African general populations are limited. Most other reports are from specific groups such as blood donors , pregnant women , men who have sex with men and HIV‐infected individuals . Prevalence and risk factors in these specific population groups may be different from the general population.…”
Section: Discussionmentioning
confidence: 99%